2022
DOI: 10.1002/jobm.202200316
|View full text |Cite
|
Sign up to set email alerts
|

Global scenario of Plasmodium vivax occurrence and resistance pattern

Abstract: Malaria caused by Plasmodium vivax is comparatively less virulent than Plasmodium falciparum, which can also lead to severe disease and death. It shows a wide geographical distribution. Chloroquine serves as a drug of choice, with primaquine as a radical cure. However, with the appearance of resistance to chloroquine and treatment has been shifted to artemisinin combination therapy followed by primaquine as a radical cure. Sulphadoxine‐pyrimethamine, mefloquine, and atovaquone‐proguanil are other drugs of choi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 96 publications
1
2
0
1
Order By: Relevance
“…The distribution of malaria types, specifically P. falciparum and P. vivax infections, was similar between patients with and without G6PD deficiency. Although no statistically significant differences were observed, the higher proportion of P. vivax infections among G6PD-deficient patients is consistent with previous studies (14,21,22) that have reported an association between G6PD deficiency and increased susceptibility to P. vivax malaria. Among the hematological parameters analyzed, the study found a noteworthy difference in the mean monocyte count between patients with G6PD deficiency and those without G6PD deficiency.…”
Section: Discussionsupporting
confidence: 91%
“…The distribution of malaria types, specifically P. falciparum and P. vivax infections, was similar between patients with and without G6PD deficiency. Although no statistically significant differences were observed, the higher proportion of P. vivax infections among G6PD-deficient patients is consistent with previous studies (14,21,22) that have reported an association between G6PD deficiency and increased susceptibility to P. vivax malaria. Among the hematological parameters analyzed, the study found a noteworthy difference in the mean monocyte count between patients with G6PD deficiency and those without G6PD deficiency.…”
Section: Discussionsupporting
confidence: 91%
“…Se aisló al paciente con el uso de mosquitero y se inició el tratamiento con solución salina intravenosa 1 L cada ocho horas, paracetamol 1 g vía intravenosa cada seis horas, oxígeno por cánula nasal a 3 L por minuto, y mebendazol 100 mg vía oral cada 12 horas; este último se suspendió por la detección del Plasmodium vivax. Se indicó la terapia antimalárica 10,11 con cloroquina 750 mg vía oral cada día (a dosis de 10 mg/kg) por dos días; luego, 375 mg vía oral al tercer día (a dosis de 5 mg/kg), acompañado de primaquina 15 mg vía oral cada día durante siete días, y acetaminofén 500 mg vía oral cada seis horas, si la temperatura corporal era mayor a 37,5 °C; sin embargo, no se reportó fiebre nuevamente. El caso fue notificado a las autoridades epidemiológicas mediante el sistema de Vigilancia Epidemiológica de El Salvador.…”
Section: Intervención Terapéuticaunclassified
“…In the genus Plasmodium , which comprises the causative agents of malaria, three metacaspases (MCA1-3) were previously identified by comparative sequence analysis [ 8 , 9 ] and studies on their expression and activity are limited to the rodent parasite P. berghei as well as to P. falciparum − the most prevalent and deadly human malaria parasite worldwide [ 10 13 ]. The frequent emergence of chemoresistance in P. falciparum parasites certainly propelled the knowledge of P. falciparum metacaspases ( Pf MCAs), while P. vivax MCAs ( Pv MCAs) have been neglected, despite P. vivax impacting significantly on public health in many malaria endemic countries outside of sub-Saharan Africa, where antimalarial drug resistance is also found in P. vivax infections [ 14 , 15 ]. Although there are published work on Pv MCAs, all of them are focused on genetic diversity of Pv MCA1 [ 16 18 ] and no study of MCA expression has been published.…”
Section: Introductionmentioning
confidence: 99%